2004
DOI: 10.1002/jccs.200400106
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Filtration of Iron(III), Copper(II) and Lead(II) Ions as 1‐(2‐Pyridylazo) 2‐Naphtol (PAN) for Their Preconcentration and Atomic Absorption Determinations

Abstract: A membrane filtration procedure for the preconcentration and atomic absorption spectrometric determination of Pb(II), Co(II) and Fe(III) ions in natural water samples has been established. Cellulose nitrate membrane filters (0.45 μm and 47 mm diameter) were used in all experiments. The procedure is based on chelate formation of the analyte metals with 1‐(2‐pyridylazo) 2‐naphtol (PAN) and on retention of the chelates on cellulose nitrate membrane filter. The cellulose nitrate membrane and analyte ions were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…6 Thus, there is a great interest concerning the implementation of a reliable preconcentration system for lead(II) for analytical determinations. 7 Several methods extensively used for preconcentration include liquid-liquid extraction, [8][9][10][11] co-precipitation, 12-14 ion exchange, solid-phase extraction [15][16][17][18][19][20] and chelating matrices. To solve the problem of main problem of FAAS and ICP-AES techniques for trace analysis, solid-phase extraction is the one of the important preconcentration method.…”
mentioning
confidence: 99%
“…6 Thus, there is a great interest concerning the implementation of a reliable preconcentration system for lead(II) for analytical determinations. 7 Several methods extensively used for preconcentration include liquid-liquid extraction, [8][9][10][11] co-precipitation, 12-14 ion exchange, solid-phase extraction [15][16][17][18][19][20] and chelating matrices. To solve the problem of main problem of FAAS and ICP-AES techniques for trace analysis, solid-phase extraction is the one of the important preconcentration method.…”
mentioning
confidence: 99%
“…Different separation and preconcentration techniques using solid phase extraction (SPE) [28], co-precipitation [29] solvent extraction [30], membrane filtration [31], cloud point extraction [32,33], flotation [34], electrochemical decomposition [35] ion exchange etc. have been developed for the trace metal ion determination.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reveals only few reports on the extraction of metal ions using calyx [4] resorcinarene and its derivatives [74][75][76][77][78][79][80]. As far as work on polymer supported calyx [4] resorcinarenes is concerned, Merdivan et al [31,81,82] have reported the use of calyx [4] resorcinarene impregnated on Amberlite XAD for separation and preconcentration of rare earths.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different techniques used for the separation and preconcentration, membrane filtration is preferred due to the low risk of contamination, the use of environmentally safe reagents, and simple methodology (Itoh et al, 1983, Gao et al, 1996, Soylak et al, 2004, Pourreza and Ghanemi 2006. If the metal ions were allowed to be directly collected in the form of metal complexes or ion-pairs on a membrane filter from an aqueous solution by filtration, this membrane filtration can be used as a rapid and simple separation and concentration technique for pretreatment of analytical samples.…”
Section: Introductionmentioning
confidence: 99%